Fatigue and Quality of Life Among Patients with Diabetes and Non-diabetes Receiving Primary Percutaneous Coronary Interventions - Shu-Fen Su; Wen-Ting Yeh (Elsevier, 2023)
s u m m a r y: Purpose: Few studies have examined the effect of diabetes mellitus (DM) on patients with coronary artery disease. The relationships between quality of life (QoL), risk factors, and DM of patients receiving percutaneous coronary interventions (PCIs) are poorly understood. We investigated the influence of DM on fatigue and QoL over time among patients receiving PCIs. Methods: An observational cohort study with a longitudinal, repeated-measures design was used to investigate fatigue and QoL among 161 Taiwanese patients with coronary artery disease with/without DM who received primary PCIs between February and December 2018. Participants provided demographic information and their Dutch Exertion Fatigue Scale and the 12-Item Short-Form Health Survey scores before the PCI and two weeks, three months, and six months post-discharge. Results: Seventy-seven PCI patients were in the DM group (47.8%; mean age = 67.7 [SD = 10.4] years). The mean scores of fatigue, physical component scale (PCS), and mental component scale (MCS) were 7.88 (SD = 6.74), 40.74 (SD = 10.05), and 49.44 (SD = 10.57), respectively. DM did not affect the magnitude of change in fatigue or QoL over time. Patients with DM perceived similar fatigue as those without DM before PCI and two weeks, three and six months post-discharge. Patients with DM perceived lower psychological QoL than those without DM two weeks post-discharge. Compared to pre-surgery scores, patients without DM perceived lower fatigue at two weeks, three months, and six months post-discharge, and higher physical QoL at three- and six-months post-discharge. Conclusions: Compared with DM patients, patients without DM had higher pre-intervention QoL and better psychological QoL two weeks post-discharge, and DM did not influence fatigue or QoL of patients receiving PCIs over six months. DM may affect patients in the long term; therefore, nurses should educate patients to regularly take medication, maintain proper habits, notice comorbidities, and follow rehabilitation regimes after PCIs to improve prognosis.